Conventional Genetic Improvement Methods in Medicinal and Aromatic Plants: A Review - Bhardwaj, Ravi; Sharma, Kamal; Sharma, Dushyant Kumar; Prakash, Prem (International Journal of Economic Plants, 2020)
The collection of medicinal and aromatic plants from the wild has been declining during the last decade; therefore it is necessary to develop highly productive cultivars, combined with appropriate cultivation and intensive agricultural techniques. Majority of the improved cultivars of medicinal and aromatic plants under cultivation have been created by conventional selection methods including individual, mass or special selection methods. Furthermore, outstanding results have been reported through hybridization and mutation. Highly productive cultivars of Mentha spicata, Ocimum americanum and Salvia officinalis have been developed through selection. Improved strains of Cymbopogon flexuosus, Melissa officinalis, Solanum laciniatum and Thymus vulagaris through intraspecific crossing resulting in changes in their active agents have been developed. Mutation breeding using physical and chemical mutagens have been successfully employed in Jasminum grandiflorum and Mentha arvensis. Hybrids of Thymus vulgaris and Artemisia annua have been developed through hybridization. According to Directorate of medicinal and aromatic plants research (DMAPR), twenty five new improved varieties of medicinal plants of fourteen species and seven varieties of aromatic plants of six species have been developed under different research institutes and Agricultural Universities in the country. Thus, improved cultivars with useful characters, resistance to biotic and abiotic stress, increased yield and early maturity have been developed through different conventional genetic improvement methods. Also hybrids with increased productivity, wider adaptability, wider application and better resistance to environmental factors have been produced through hybridization.